COMPARATIVE CHARACTERISTICS OF GENETIC PARAMETERS D-SYSTEMS OF BLOOD TYPE IN STALLIONS OF NOVOALEKSANDROVSKAYA HEAVY AND TORI BREEDS - Бровко, Олексій (Modern engineering and innovative technologies, 2024)
In Ukraine, the novoaleksandrovskaya and tory horse breeds are among the few breeds. This in turn creates a problem of conservation and effective breeding. And our task in working with these breeds is to preserve valuable stock, improve breeding qualitie